ANALYSIS OF FLEXIBLE PAVEMENT THICKNESS AT THE 3 NORTH RING ROAD JUNCTION- 3 GOLF ROAD-KASTURI ROAD IN BANJARBARU CITY - M. Riswandi; Yasruddin Yasruddin (Universitas Lambung Mangkurat, 2022)
On the Simpang 3 north ring road - Simpang 3 Jalan Golf - Jalan Kasturi which is the access road to the new Syamsudin Noor airport which is an international airport which will experience an increase in passengers which will result in an increase in traffic volume. This study aims to obtained flexible pavement thickness using the Road Pavement Design Manual Number 02/M/BM/2017 compared to PT T-01-2002-B and predict the remaining pavement life against traffic increases that occur in the coming year. then plan complementary buildings and road equipment and calculate the cost budget plan using the 2016 AHSP.From the calculation results of the 2 methods there are differences in the thickness of the flexible pavement. In the calculation of flexible pavement thickness using the Road Pavement Design Manual method no. 02/M/BM/2017 namely AC WC = 4 cm; AC Binder = 6 cm; AC Base = 8CM; LPA = 30 cm and CBR Subgrade= 0.73% with Support Layer = 1550. As for the calculation, results of the Pt T-01- 2002-B method, the results obtained are AC-WC pavement thickness = 4 cm, AC BC = 6 cm, AC Base = 15 cm, LPB = 15 cm. In addition, in writing this final project, it also discusses predicting the remaining life of the pavement and then planning complementary buildings and road equipment, for the results of the budget plan (RAB) with the result: Rp. 33,550,716,390.78 -Keywords: Road Pavement Design Manual Number 02/M/BM/2017, prediction of remaining pavement, Complementary Buildings and Road Equipment, Cost Budget Plan.